Local Wisdom of Making "Gula Habang" in Balangan Regency: Ethnoscience Study - Misbah, Misbah; Zulfah, Raihanah; Hariani, Maya; Purwasih, Desy; Umar, Fadilah; Harto, Muhdi; Muhammad, Nurlaela (KnE Social Sciences, 2024)
Ethnoscience is a science learning approach based on local wisdom, such as making Gula Habang, which is closely related to the material of temperature and heat in physics subjects. The process of making brown sugar contains a lot of genuine science, which basically can be explained scientifically, namely the concepts of temperature and heat. The research objective is to analyze original science and scientific science in the manufacture of brown sugar. This study uses direct observation about making “Gula Habang” and analysis of the temperature and heat modules based on local wisdom in the manufacture of Gula Habang. The results of the literature study and the analysis carried out by the researchers, the matter of temperature and heat can be explained by linking the concepts of temperature, change of state, and heat transfer to the process of making brown sugar. Therefore, the ethno-science-based learning of making Gula Habang, in Balangan Regency can be applied in learning physics on temperature and heat materials as well as science on heat transfer materials, because it can accommodate basic competencies in the 2013 curriculum for high school and junior high school levels, as well as learning outcomes in the independent curriculum for junior and senior high school. Keywords: local wisdom, Gula Habang, Balangan, ethnoscience study